Time-resolved morphological and transcriptomic characterization of early enteric neuron subtype emergence in chick - Maëlys André; Raphael Gury; Maxime Lepetit; Franck Boismoreau; Muriel Bozon; Jérémy Ganofsky; Cassandre Heritier-Tellier; Ingrid Plotton; Rémi Duclaux-Loras; Noël Peretti; Guillaume Marcy; Valérie Castellani; et al. (Proceedings of the National Academy of Sciences, 2026)
The genetic programs directing nascent enteric nervous circuits and their unique architecture remain poorly characterized. To gain insight, we combined manipulations in the chick embryo model, whole gut three-dimensional (3D) imaging, and single-nucleus transcriptomics at very short intervals for time-resolved analyses of neuronal subtype trajectories. In imaging, we found highly dynamic axon network growth, with rapid increase in axon density and spatial orientation diversification. At transcriptomic levels, we correlated these changes to cell-state transitions with specific axon guidance gene sets. Cross-analyses with human and mouse embryo scRNAseq and expression profiles revealed globally conserved enteric lineage trajectories and subtypes specific axon guidance programs in all species. Finally, manipulation of DSCAM and ISLR2 evolutionary conserved networks in chick whole gut cultures altered enteric axon patterns, validating our paradigm and its applicability to advance current knowledge on human enteric circuit wiring.